2010
DOI: 10.1098/rsta.2010.0187
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis and controller synthesis for hybrid dynamical systems

Abstract: Wherever continuous and discrete dynamics interact, hybrid systems arise. This is especially the case in many technological systems in which logic decision-making and embedded control actions are combined with continuous physical processes. Also for many mechanical, biological, electrical and economical systems the use of hybrid models is essential to adequately describe their behaviour. To capture the evolution of these systems, mathematical models are needed that combine in one way or another the dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 90 publications
0
54
0
Order By: Relevance
“…condition is verified by means of Fig. 9, which represents the polar plot of G(s) as in (13), showing that ρRe(G(jω)) > −1, for ρ > 1 is met for all ω ∈ R with sufficient margins to account for plant uncertainty. In this respect, note that the user can influence Re(G(jω)), and thus condition (II) in Theorem IV.1, by means of the design of C 0 (s) and C 1 (s).…”
Section: A Design Of the Proposed Scheduled Controllermentioning
confidence: 95%
See 2 more Smart Citations
“…condition is verified by means of Fig. 9, which represents the polar plot of G(s) as in (13), showing that ρRe(G(jω)) > −1, for ρ > 1 is met for all ω ∈ R with sufficient margins to account for plant uncertainty. In this respect, note that the user can influence Re(G(jω)), and thus condition (II) in Theorem IV.1, by means of the design of C 0 (s) and C 1 (s).…”
Section: A Design Of the Proposed Scheduled Controllermentioning
confidence: 95%
“…9. Polar plot of G(jω) as in (13) in which the dashed line represents −1. condition is verified by means of Fig.…”
Section: A Design Of the Proposed Scheduled Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the model constructed above, the optimal scheduling is computed through model predictive control (MPC; see Bemporad & Morari 1999;Heemels et al 2010 for details). For simplicity, we assume that we can observe the internal state x.…”
Section: (B) Model Predictive Controlmentioning
confidence: 99%
“…Reviews dedicated to some specific applications of hybrid models can also be found, for example in biological networks modelling [12], in cancer modelling [10,21,30,40], and more specifically tumour growth [24,29], tumour immunology [41], brain cancer [42] or angiogenesis [16]. Many special issues or reviews are also dedicated to the more specific field of hybrid systems [2,17,31,39] which can be considered as a subclass of hybrid models mainly (but not only) related to the field of automatic control.…”
Section: Introductionmentioning
confidence: 99%